Visual Capture of a Tactile Sensation is Influenced by Repeated, Structured Exposure of a Visual Stimulus in Virtual Reality - Willis, Dion; Stevens, Brett; Powell, Wendy (Frontiers in Virtual Reality, 2021)
Phantom limb pain is commonly known as a neurological condition, where an amputee will continue to feel a painful limb that is no longer present. Virtual mirror therapy (VMT) has shown promising results for alleviating phantom limb pain. Additionally, the inclusion of tactile sensation in VMT has shown to increase the efficacy of pain management; however, delivering a tactile sensation to a phantom limb, without the use of invasive procedures, can be difficult. The current approach for transferring a tactile sensation to a phantom limb is called visual capture. The ability to establish visual capture has been demonstrated in VMT applications, however, there is little research into whether an established visual capture effect can be relocated to a more distal location for phantom limb pain management. This paper investigates whether a passive vibrotactile sensation can be moved to a distal location from its veridical location using a series of distally located lights presented in either a random or a structured fashion. Eight non-amputee participants were tasked with localising a static tactile sensation on a virtual arm. These vibrotactile sensations were presented simultaneously with a visual light stimulus, either co-located or located distally at three different locations. Findings show that a tactile sensation without a visual stimulus was difficult for participants to localise; however, when a visual stimulus was added, they were better able to locate the veridical tactile position. The structured group exhibited a larger range of tactile relocation responses than the random group. However, this result was unreliable, with the majority of the responses situated at the vibrotactile actuator. There was a significant difference between the random and structured group's ability to retain a visual capture at the veridical vibrotactile location when the lights were located distally. The random group did not express a visual capture response when the lights were presented distally while the structured group did, suggesting the structured group developed a more robust association between the visual stimulus and the vibrotactile stimulus. Findings may be of use where increasing tactile acuity without significant alteration of a veridical location is a desired therapeutic outcome.